(untitled) (The Macau Ricci Institute Journal, 2023)
The essay explores the prospects for Dialogue with China, by surveying the history of the Red Cross Movement in China through the four periods of its modern history. The author adopts the four propositions for dialogue outlined by Xi Jinping, and then, in light of the Red Cross history, proposes two other propositions, to assist dialogues when challenges and difficulties are encountered along the way. This sketch of the Red Cross Movement in China demonstrates the importance of patience and reciprocity for sustaining any cross-cultural dialogue.